Understanding consumer’s intention to purchase the green product: The role social media marketing - Wong, Jia Yie; Tan, Zijian (2024)
The objective for this study is to examine the factors that influencing the green purchase intention. The theory that we adopted is “Theory of planned behaviour” (TPB). Furthermore, Attitude (ATT), Subjective norm (SM), Perceived behavioural Control (PBC) and Social Media Marketing (SMM) are the independent variables in this study. These independent variables are utilized to assess whether it have the significantly influence the Green Purchase Intention (GPI)- Dependent variable Moreover, total of 251 respondents were collected in this study. The Statistical Software Package for Social Sciences (SPSS) was adopted to analyse the IVs and also IVs. The findings showed that Attitude (ATT), Social Media Marketing (SMM) have significant influence the green purchase intention. Whereas Subjective Norm and Perceived behavioural control (PBC) have insignificant influence of green purchase intention. The relationship between the IV and DV was using Reliability test. In addition, the inferential analysis was using are the Pearson Correlation Coefficient and Multiple Regression Analysis. This study able to offer the fresh knowledge for the researcher and business to understanding the factors influencing green purchase intention. keywords: purchase intention, green product, generation Z, social media marketing, attitude, subjective norm, perceived control behavior, green product industry Subject Area: HF5410-5417.5 Marketing. Distribution